2021
DOI: 10.3389/fimmu.2021.695238
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transport and Metabolism in Myeloid Function

Abstract: Regulation of amino acid availability and metabolism in immune cells is essential for immune system homeostasis and responses to exogenous and endogenous challenges including microbial infection, tumorigenesis and autoimmunity. In myeloid cells the consumption of amino acids such as arginine and tryptophan and availability of their metabolites are key drivers of cellular identity impacting development, functional polarization to an inflammatory or regulatory phenotype, and interaction with other immune cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…[ 35 ] Glutamine metabolism has also been reported to be critical for the recruitment and functional activity of MDSCs. [ 36 ] Glutamine antagonism has successfully resulted in reduced MDSC infiltration into the TME. [ 10 , 36 ] We found that JHU083 inhibited M‐MDSCs in our tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] Glutamine metabolism has also been reported to be critical for the recruitment and functional activity of MDSCs. [ 36 ] Glutamine antagonism has successfully resulted in reduced MDSC infiltration into the TME. [ 10 , 36 ] We found that JHU083 inhibited M‐MDSCs in our tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Glutamine antagonism has successfully resulted in reduced MDSC infiltration into the TME. [ 10 , 36 ] We found that JHU083 inhibited M‐MDSCs in our tumor model. The inhibition of glutamine metabolism and OXPHOS enhanced apoptosis and autophagy pathways, which could be the potential reason for the decrease in M‐MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of arginine serves as a key regulator of innate and adaptive immunity [ 7 , 8 , 9 , 10 , 11 ]. Arginine catabolism in myeloid cells is largely driven by nitric oxide (NO) synthase (NOS) and arginase (ARG), and the differential regulation of these enzymes augments or diminishes the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we strengthened this finding in another group of experiments with BMDMs separated from GBM samples (Figure 2B) and confirmed it in an in vitro model of immunosuppressive macrophages derived from blood monocytes of HDs (Figure 2B, Mφ), whose relevant suppressive activity and HO‐1 expression (Figure S1) justified their use in investigating HO‐1‐related immunosuppressive mechanisms. Previous studies from us and others identified the contribution of the IDO1 and ARG‐1 enzymes in different immunosuppressive myeloid populations 7,20,21 . For this reason, we evaluated the effect of the IDO1 inhibitor 1‐MT and ARG‐1/ARG‐2 inhibitor Nor‐NOHA (NN).…”
Section: Resultsmentioning
confidence: 99%